Preparation method of hydrophilic / hydrophobic double-layer nanofiber membrane with full-degradable characteristic
The preparation of fully degradable/hydrophobic double-layer nanofiber membranes through electrospinning technology solves the shortcomings of traditional nanofiber membranes in terms of biodegradability and functionalization, realizes the composite function and good biodegradation performance of membrane materials, and is suitable for applications in the field of biomedical medicine.
Patent Information
- Application Number
- CN202411943052.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-26
- Publication Date
- 2025-03-28
- Estimated Expiration
- 2044-12-26
AI Technical Summary
Traditional nanofiber membranes have shortcomings in biodegradability and functionalization, and it is difficult to achieve a balance between hydrophilicity and hydrophobicity, which affects its comprehensive performance and application life.
Fully degradable/hydrophobic bilayer nanofiber membranes are prepared through electrospinning technology. Highly biocompatible degradable materials such as polylactic acid-glycolic acid copolymer (PLGA), polyethylene glycol monomethyl ether (mPEG) and carbon dots (CDs) are used to regulate the composition and structure of the two-layer films to achieve the composite function of the membrane material.
It has achieved the multifunctionalization and optimization of degradability of nanofiber membranes, and has good biodegradability and antibacterial and anti-inflammatory properties. It is suitable for the promotion of surface skin wound healing and wound repair of urethral inner wall wounds.
Smart Images

Figure CN119711050A_ABST
Abstract
Description
Technical Field
[0001] The present invention specifically relates to the preparation of an electrospun nanofiber membrane, and in particular to a fully degradable hydrophilic / hydrophobic double-layer electrospun nanofiber membrane, belonging to the field of preparation of novel bio-nanomaterials. Background Art
[0002] As a new type of high-performance material, nanofiber material has a high specific surface area, rich pore structure, and excellent mechanical properties, and has become the choice of many application fields. In recent years, nanofiber membranes have been widely used in water treatment, air filtration, tissue engineering, drug delivery, sensors, and environmental governance. In particular, electrospinning technology has become one of the main methods for preparing nanofiber membranes because it can produce fibers with diameters ranging from nanometers to micrometers. Among them, although traditional nanofiber membranes have micrometer-level fiber diameters and excellent mechanical properties, they often have the problem of poor biodegradability. On the other hand, traditional nanofiber membranes also have certain limitations in terms of functionalization. For example, the nanofiber membrane structure of a single material is difficult to achieve a balance between hydrophilicity and hydrophobicity, which affects the comprehensive performance and application life of the membrane material. Based on the current situation, the present invention proposes a design scheme for a nanofiber membrane with a double-layer structure, that is, by regulating the composition and structure of the two-layer membrane, the composite functions of the membrane material, such as hydrophilicity and hydrophobicity, are realized, and further by adopting a highly biocompatible degradable material, its biodegradability is improved, which has good application prospects in the biological field.
[0003] The hydrophilic / hydrophobic double-layer nanofiber membrane can meet multiple needs in different scenarios by designing hydrophilic and hydrophobic materials into a two-layer structure. For example, the hydrophobic layer can improve the waterproofness of the nanofiber membrane, while the hydrophilic layer helps to improve its adsorption capacity. The hydrophilic / hydrophobic double-layer structure can flexibly adjust the physical properties of the nanofiber membrane according to actual needs and expand its scope of application in various applications.
[0004] The present invention aims to realize the multifunctionalization of nanofiber membranes and the optimization of degradable properties by rationally selecting degradable polymer materials. The electrostatic spinning technology is used to prepare a fully degradable hydrophilic / hydrophobic double-layer nanofiber membrane, which can not only meet the needs of biodegradation, but also has strong application value. And by adding carbon dots (CDs), the hydrophilic layer has excellent antibacterial and anti-inflammatory properties. By selecting a suitable spinning solution ratio, a reasonable combination of the hydrophilic layer and the hydrophobic layer can be achieved, thereby giving the nanofiber membrane material multiple functions, meeting the needs of promoting surface skin wound healing, urethral wall wound repair and other biological fields, and has broad market prospects and application potential. Summary of the invention
[0005] The present invention provides a method for preparing a fully degradable hydrophilic / hydrophobic double-layer nanofiber membrane based on electrospinning, which solves the demand for biofunctional application of nanofiber membrane materials in the prior art, and discloses the selection and debugging of the prepared fully degradable hydrophilic / hydrophobic double-layer nanofiber membrane, so that it has good application prospects.
[0006] Based on this, the present invention provides a method for preparing a fully degradable hydrophilic / hydrophobic double-layer nanofiber membrane based on electrospinning. The specific steps are as follows:
[0007] Step 1: Poly(lactic acid-co-glycolic acid) (PLGA), polyethylene glycol monomethyl ether (mPEG) and carbon dots (CDs) are uniformly dissolved in hexafluoroisopropanol and stirred with a magnetic stirrer to a uniform light yellow solution as the spinning solution of the hydrophilic layer;
[0008] Step 2: Dissolve polycaprolactone (PCL) evenly in hexafluoroisopropanol and stir with a magnetic stirrer until it is completely dissolved into a transparent solution as the spinning solution for the hydrophobic layer;
[0009] Step 3: using the solution of step 1 as spinning solution, electrospinning the hydrophilic layer nanofiber membrane through an electrospinning machine;
[0010] Step 4: Using the solution of step 2 as the spinning solution, electrospinning of the hydrophobic layer nanofiber membrane is continued on the basis of the hydrophilic layer nanofiber membrane of step 3, and finally a hydrophilic / hydrophobic double-layer nanofiber membrane is obtained.
[0011] Furthermore, in step 1, CDs are prepared using polyethyleneimine (PEI), citric acid, and glutathione as raw materials, and dissolved in hexafluoroisopropanol for later use at a concentration of 0.15 g / mL.
[0012] Furthermore, the molecular weight of mPEG in step 1 is 1000-4000 g / mol.
[0013] Further, in step 1, the amount of PLGA added is 0.75-1.5 g, the amount of mPEG added is 0.25-0.6 g, the amount of organic solvent hexafluoroisopropanol is 4.5-10 mL, and the amount of CDs added is 0.5-1 mL;
[0014] Further, in step 2, the amount of PCL added is 0.8 to 1.8 g, and the amount of the organic solvent hexafluoroisopropanol is 6.6 to 13.2 g;
[0015] The spinning solution of the hydrophilic layer and the hydrophobic layer is obtained by adopting the preparation method.
[0016] The hydrophilic layer and the hydrophobic layer spinning solution are used to prepare a fully degradable hydrophilic / hydrophobic double-layer nanofiber membrane based on an electrostatic spinning machine.
[0017] Compared with the prior art, the present invention has the following beneficial effects:
[0018] In the present invention, the hydrophilicity of the hydrophilic layer is enhanced by the addition of mPEG, and the antioxidant performance of the hydrophilic layer nanofiber membrane can be enhanced by the addition of CDs, which has application potential in wound dressings. Secondly, the organic solvent of the hydrophobic layer and the organic solvent of the hydrophilic layer are both hexafluoroisopropanol, which makes it easier to reasonably match the hydrophilic / hydrophobic double-layer nanofiber membrane. Based on electrospinning, the solution is formed into a nanofiber membrane through high-voltage electrospinning. The nanofiber has a high specific surface area and porosity, so that the carbon dots are evenly attached to the fiber surface and are not easy to agglomerate, which is conducive to exerting the performance of the carbon dots in the application scenario.
[0019] The hydrophilic / hydrophobic double-layer nanofiber membrane of the present invention greatly ensures the uniform attachment of carbon dots to the hydrophilic layer. The hydrophilic layer helps to resist oxidation and heal wounds due to the addition of CDs, and the hydrophobic layer helps to ensure that the wound is isolated from the external environment, ensuring the function of CDs in the hydrophilic layer. The nanofiber membrane is a fully degradable material and can also be used for antibacterial, anti-inflammatory and wound healing in parts such as the urethra. By batch preparing fully degradable hydrophilic / hydrophobic double-layer nanofiber membranes, it can be applied to biomedicine. BRIEF DESCRIPTION OF THE DRAWINGS
[0020] Figure 1 Schematic diagram of water contact angle on the surface of hydrophobic nanofiber membrane prepared by electrospinning in Example 6
[0021] Figure 2 Schematic diagram of water contact angle on the surface of hydrophilic nanofiber membrane prepared by electrospinning in Example 6
[0022] Figure 3 Schematic diagram of the surface morphology of the hydrophobic layer nanofiber membrane prepared by electrospinning in Example 6.
[0023] Figure 4 Schematic diagram of the surface morphology of the hydrophilic layer nanofiber membrane prepared by electrospinning in Example 6.
[0024] Specific implementation examples
[0025] The present invention is described in detail and clearly below. Although the examples described are only some of the examples of the present invention and do not represent all the examples, they can also enable technicians to have a deep understanding of the advantages and features of the present invention. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0026] The following experimental methods, unless otherwise specified, are conventional methods; the following raw materials and reagents, unless otherwise specified, are commercially available.
[0027] Example 1
[0028] Step 1: Weigh 1.5 g PLGA and 0.6 g mPEG with a molecular weight of 1000 g / mol; then weigh 10 mL hexafluoroisopropanol and 1 mL CDs, and stir with a magnetic stirrer until they are completely dissolved to obtain a uniform light yellow solution;
[0029] Step 2: Weigh 0.8 g of PCL with a molecular weight of 80,000 g / mol, and continue to weigh 9.2 g of hexafluoroisopropanol, and stir with a magnetic stirrer until a uniform transparent solution is obtained;
[0030] Step 3: using the solution in step 1 as a hydrophilic layer spinning solution, synthesizing a hydrophilic layer nanofiber membrane through an electrospinning machine;
[0031] Step 4: Using the solution in step 2 as the spinning solution for the hydrophobic layer, a hydrophobic layer nanofiber membrane is synthesized on the basis of the hydrophilic layer nanofiber membrane in step 3 by an electrospinning machine.
[0032] The contact angle of the hydrophilic layer nanofiber membrane prepared in this example is 27°, and the contact angle of the hydrophobic layer nanofiber membrane is 101°.
[0033] Example 2
[0034] Step 1: Weigh 1.5 g PLGA and 0.6 g mPEG with a molecular weight of 1000 g / mol; then weigh 10 mL hexafluoroisopropanol and 1 mL CDs, and stir with a magnetic stirrer until they are completely dissolved to obtain a uniform light yellow solution;
[0035] Step 2: Weigh 1.6 g of PCL with a molecular weight of 80,000 g / mol, and continue to weigh 18.4 g of hexafluoroisopropanol, and stir with a magnetic stirrer until a uniform transparent solution is obtained;
[0036] Step 3: using the solution in step 2 as a hydrophobic layer spinning solution, synthesizing a hydrophobic layer nanofiber membrane through an electrospinning machine;
[0037] Step 4: Using the solution in step 1 as the spinning solution for the hydrophilic layer, continue electrospinning to synthesize the hydrophilic layer nanofiber membrane based on the hydrophobic layer nanofiber membrane in step 3.
[0038] The contact angle of the hydrophilic layer nanofiber membrane prepared in this example is 27°, and the contact angle of the hydrophobic layer nanofiber membrane is 101°.
[0039] Example 3
[0040] Step 1: Weigh 1.5 g PLGA and 0.5 g mPEG with a molecular weight of 1000 g / mol; then weigh 9 mL hexafluoroisopropanol and 1 mL CDs, and stir with a magnetic stirrer until they are completely dissolved to obtain a uniform light yellow solution;
[0041] Step 2: Weigh 1.8 g of PCL with a molecular weight of 80,000 g / mol, and continue to weigh 13.2 g of hexafluoroisopropanol, and stir with a magnetic stirrer until a uniform transparent solution is obtained;
[0042] Step 3: using the solution in step 2 as a hydrophobic layer spinning solution, synthesizing a hydrophobic layer nanofiber membrane through an electrospinning machine;
[0043] Step 4: Using the solution in step 1 as the hydrophilic layer spinning solution, continue electrospinning to synthesize the hydrophilic layer nanofiber membrane based on the hydrophobic layer nanofiber membrane in step 3.
[0044] The contact angle of the hydrophilic layer nanofiber membrane prepared in this example is 22°, and the contact angle of the hydrophobic layer nanofiber membrane is 101°.
[0045] Example 4
[0046] Step 1: Weigh 1.5 g PLGA and 0.5 g mPEG with a molecular weight of 4000 g / mol; then weigh 5 mL hexafluoroisopropanol and 1 mL CDs, and stir with a magnetic stirrer until they are completely dissolved to obtain a uniform light yellow solution;
[0047] Step 2: Weigh 1.8 g of PCL with a molecular weight of 80,000 g / mol, and continue to weigh 13.2 g of hexafluoroisopropanol, and stir with a magnetic stirrer until a uniform transparent solution is obtained;
[0048] Step 3: using the solution in step 1 as a hydrophilic layer spinning solution, synthesizing a hydrophilic layer nanofiber membrane through an electrospinning machine;
[0049] Step 4: Using the solution in step 2 as the spinning solution for the hydrophobic layer, a hydrophobic layer nanofiber membrane is synthesized on the basis of the hydrophilic layer nanofiber membrane in step 3 by an electrospinning machine.
[0050] The contact angle of the hydrophilic layer nanofiber membrane prepared in this example is 17°, and the contact angle of the hydrophobic layer nanofiber membrane is 101°.
[0051] Example 5
[0052] Step 1: Weigh 1.5 g PLGA and 0.5 g mPEG with a molecular weight of 4000 g / mol; then weigh 6 mL hexafluoroisopropanol and 1 mL CDs, and stir with a magnetic stirrer until they are completely dissolved to obtain a uniform light yellow solution;
[0053] Step 2: Weigh 0.9 g of PCL with a molecular weight of 80,000 g / mol, and continue to weigh 6.6 g of hexafluoroisopropanol, and stir with a magnetic stirrer until a uniform transparent solution is obtained;
[0054] Step 3: Using the solution in step 1 as a spinning solution for a hydrophilic layer, synthesizing a nanofiber membrane with a hydrophilic layer through an electrospinning machine;
[0055] Step 4: Using the solution in step 2 as the spinning solution for the hydrophobic layer, a hydrophobic layer nanofiber membrane is synthesized on the basis of the hydrophilic layer nanofiber membrane in step 3 by an electrospinning machine.
[0056] The contact angle of the hydrophilic layer nanofiber membrane prepared in this example is 30°, and the contact angle of the hydrophobic layer nanofiber membrane is 101°.
[0057] Example 6
[0058] Step 1: Weigh 1.5 g PLGA and 0.5 g mPEG with a molecular weight of 4000 g / mol; then add 6 mL hexafluoroisopropanol and 1 mL CDs, and stir with a magnetic stirrer for 4 to 5 hours until completely dissolved to obtain a uniform light yellow solution;
[0059] Step 2: Weigh 0.9 g of PCL with a molecular weight of 80,000 g / mol, and continue to weigh 6.6 g of hexafluoroisopropanol, and stir with a magnetic stirrer for 5 to 6 hours until a uniform transparent solution is obtained;
[0060] Step 3: using the solution in step 1 as the hydrophilic layer spinning solution, synthesizing a hydrophilic layer nanofiber membrane with CDs through an electrospinning machine;
[0061] Step 4: Using the solution in step 2 as the spinning solution for the hydrophobic layer, a hydrophobic layer nanofiber membrane is synthesized by an electrospinning machine at the flow rate set in step 3 and on the basis of the hydrophilic layer nanofiber membrane with CDs.
[0062] The contact angle of the hydrophilic layer nanofiber membrane prepared in this example is 41°, and the contact angle of the hydrophobic layer nanofiber membrane is 101°.
[0063] Example 7
[0064] Step 1: Weigh 0.75 g PLGA and 0.25 g mPEG with a molecular weight of 4000 g / mol; then weigh 4.5 mL hexafluoroisopropanol and 0.5 mL CDs, and stir with a magnetic stirrer until they are completely dissolved to obtain a uniform light yellow solution;
[0065] Step 2: Weigh 1.8 g of PCL with a molecular weight of 80,000 g / mol, and continue to weigh 13.2 g of hexafluoroisopropanol, and stir with a magnetic stirrer until a uniform transparent solution is obtained;
[0066] Step 3: using the solution in step 1 as a hydrophilic layer spinning solution, synthesizing a hydrophilic layer nanofiber membrane through an electrospinning machine;
[0067] Step 4: Using the solution in step 2 as the hydrophobic layer spinning solution, a hydrophobic layer nanofiber membrane is synthesized by an electrospinning machine based on the hydrophilic layer nanofiber membrane in step 3.
[0068] The contact angle of the hydrophilic layer nanofiber membrane prepared in this example is 54°, and the contact angle of the hydrophobic layer nanofiber membrane is 101°. Characterization tests were performed on the hydrophilic / hydrophobic nanofiber membrane samples in Example 6, and the results showed that:
[0069] See also Figure 1 , Figure 1 This is a schematic diagram of the surface water contact angle of the hydrophobic layer electrospun nanofiber membrane sample prepared in Example 6. It can be seen from the figure that the hydrophobic layer contact angle is 101°.
[0070] See also Figure 2 , Figure 2 This is a schematic diagram of the surface water contact angle of the hydrophilic layer electrospun nanofiber membrane sample prepared in Example 6. It can be seen from the figure that the contact angle of the hydrophilic layer is 41°.
[0071] See also Figure 3 , Figure 3 This is a schematic diagram of the surface morphology of the hydrophobic layer electrospun nanofiber membrane sample prepared in Example 6. It can be seen from the figure that the surface of the nanofibers is smooth and evenly distributed.
[0072] See also Figure 4 , Figure 4 This is a schematic diagram of the surface morphology of the hydrophilic layer electrospun nanofiber membrane sample prepared in Example 6. From the figure, it can be seen that the surface of the nanofibers is smooth and evenly distributed.
[0073] The above results indicate that the fully degradable hydrophilic / hydrophobic double-layer nanofiber membrane of the present invention was successfully prepared by electrospinning, wherein the addition of carbon quantum dots improved the antibacterial and anti-inflammatory properties of the nanofiber membrane, and the addition of superhydrophilic precursors improved the hydrophilic properties of the hydrophilic layer. Therefore, the preparation of the fully degradable double-layer nanofiber membrane can be applied to biomedicine to promote wound healing.
[0074] Although the embodiments of the present invention are disclosed above, their application is not limited to the description and implementation methods. It can be fully applied to various fields suitable for the present invention. For those familiar with the art, additional modifications can be easily implemented. Therefore, without departing from the general concept defined by the claims and the equivalent scope, the present invention is not limited to specific details.
Claims
1. A method for preparing a fully degradable hydrophilic / hydrophobic double-layer nanofiber membrane, characterized in that: The following steps are involved: Step 1: Poly(lactic acid-co-glycolic acid) (PLGA), polyethylene glycol monomethyl ether (mPEG) and carbon dots (CDs) are uniformly dissolved in hexafluoroisopropanol and stirred with a magnetic stirrer to a uniform light yellow solution as the spinning solution for the hydrophilic layer; Step 2: Dissolve polycaprolactone (PCL) in hexafluoroisopropanol uniformly and stir with a magnetic force until it is completely dissolved to obtain a transparent solution as the spinning solution for the hydrophobic layer; Step 3: using the solution of step 1 as a hydrophilic layer spinning solution, and performing electrospinning through an electrospinning machine to obtain a hydrophilic layer nanofiber membrane; Step 4: Using the solution of step 2 as the spinning solution for the hydrophobic layer, electrospinning of the hydrophobic layer nanofiber membrane is performed on the basis of the hydrophilic layer nanofiber membrane of step 3, and finally obtaining a hydrophilic / hydrophobic double-layer nanofiber membrane.
2. The preparation method according to claim 1, characterized in that The CDs described in step 1 are prepared using polyethyleneimine (PEI), citric acid, and glutathione as raw materials, and are dissolved in hexafluoroisopropanol for later use at a concentration of 0.15 g / mL.
3. The preparation method according to claim 1, characterized in that The molecular weight of the mPEG described in step 1 is 1000-4000 g / mol.
4. The preparation method according to claim 1, characterized in that The amount of the organic solvent hexafluoroisopropanol added in step 1 is 4.5-10 mL, the amount of PLGA added is 0.75-1.5 g, the amount of mPEG added is 0.25-0.6 g, and the amount of CDs added is 0.5-1 mL.
5. The preparation method according to claim 1, characterized in that In step 2, the amount of PCL added is 0.8-1.8 g, and the amount of the organic solvent hexafluoroisopropanol is 6.6-13.2 g.
6. The preparation method according to claim 1, characterized in that The contact angle of the hydrophilic layer nanofiber membrane in step 3 is 17-54°, and the contact angle of the hydrophobic layer nanofiber membrane in step 4 is 101°.
Citation Information
Patent Citations
Preparation method of modified PLGA-PEG nano-fiber blanket
CN103266419A
Multi-drug phased continuous controlled-release drug delivery system and preparation method thereof
CN109908359A
Method for preparing high-hydrophobicity film by electrostatic spinning
CN110820172A
Method for detecting Hg < 2 + > and glutathione by using off-on fluorescence sensor
CN115494042A
Recombinant mouse antibacterial peptide composite nano antibacterial dressing and preparation method thereof
CN116920157A
Cited By
Carbon quantum dot gel material based on front-end polymerization means and preparation method and application of composite film of carbon quantum dot gel material
CN120888027A
A preparation method and application of a carbon quantum dot gel material based on a front-end aggregation means and a composite film thereof
CN120888027B